2016
DOI: 10.1007/s10228-016-0526-7
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle differences between two species of genus Pempheris based on age determination around Okinawa-jima Island

Abstract: To clarify the life cycles of two species of genus Pempheris around Okinawa-jima Island, age and growth were examined using sectioned otolith. Monthly changes in the appearance frequency of an opaque ring on the outer margin of the sagittal otolith indicated that ring formation occurred once a year from April to June in both species. Ages were determined based on the number of opaque rings on the sectioned otolith, and the maximum ages observed for Pempheris schwenkii and Pempheris adusta were 6 and 16 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The size of the G. aculeatus in this study was tightly correlated with their inferred age, and both age and L S correlated with larger otolith size, supporting our inferences about the relationship between otolith development and age. The positive relationships of age, L S and otolith size in fishes have been reported widely by previous researchers (Harvey et al ., ; Koeda et al ., ; Williams & Bedford, ). A test by Harvey et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The size of the G. aculeatus in this study was tightly correlated with their inferred age, and both age and L S correlated with larger otolith size, supporting our inferences about the relationship between otolith development and age. The positive relationships of age, L S and otolith size in fishes have been reported widely by previous researchers (Harvey et al ., ; Koeda et al ., ; Williams & Bedford, ). A test by Harvey et al .…”
Section: Discussionmentioning
confidence: 99%
“…A test by Harvey et al (2000) on 63 species of fish found that 45 of them exhibited a linear relationship between body size and otolith size. Since size of fish also correlates positively with their age (Koeda et al, 2016), it is reasonable to expect a linear correlation between age and otolith size. However, we found there was an apparent inconsistency in the relationship between age and L S in the Bhar population, where 2 year old fish were smaller than yearlings.…”
Section: Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of 60 individuals being kept in the aquarium and observations being carried out during their spawning season, the spawning behavior was observed only once in 3 days. This observation may be attributed to several possible reasons: they are too old for spawning (more than 8 years old), whereas the maximum age has been estimated to be 6 years old, and most of the individuals younger than 2 years old in nature ( Koeda et al, 2016 ); the spawning season ended in the tank, since the spawning season is estimated to be January to June ( Koeda, Ishihara & Tachihara, 2012 ) and observations were made in late May and June; or spawning was suppressed due to the stress of the aquarium environment.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few swimming fish groups, such as Clupeidae and Atherinidae, may compete for this rich food resource with Pempheridae ( Hobson, 1974 ). Koeda et al (2016) compared the age and growth of P. schwenkii and P. adusta in the Okinawa Island, and indicated that the growth coefficient (K) of P. schwenkii was significantly higher than those of other reef fishes and that the species can grow up to more than 80% of their maximum length in the first year. In addition, Koeda, Ishihara & Tachihara (2012) indicated the spawning of P. schwenkii was not related to the lunar cycle, and occurred more frequently compared to other reef fishes.…”
Section: Discussionmentioning
confidence: 99%